Brief history of surfactants, their applications, and research in Nepal - Dhakal, Rajendra; Basnet, Nabin; Bhattarai, Ajaya (Damak Campus Journal, 2024)
This article reviews on the origination and development of soaps (later called surfactants) and their applications in human civilization. It was reviewed that soaps were came in use in human life as earlier as 2200 BC in Babylon. In ancient time, soaps were prepared using tallow and ashes in most of the region of world, and in similar way China began to use plats and herbs to make soaps. The soaps later called surfactants were alkali metal soaps, which have been around for thousands of years. The first recorded reference to soaps as cleaning agents dates back to 200 AD, which was prepared by Galen (Greek Physician) using fat, ash lye and lime. Nowadays, the words soap, detergent and surfactant are synonymously used. These compounds are manufacturing in large amount using plants, animals and by synthetic method. These compounds have great importance in domestic, industrial, medicinal, and synthetic applications in our daily life.Currently, the global market value is about 40 Billion USD in 2024 and is expected to meet about 60 Billion USDby 2033. Surfactants are widely used in the field of research in Nepal. A summary of surfactant research from 2009 to now is also included in this article.